Adipocyte Ceramides—The Nexus of Inflammation and Metabolic Disease - Chaurasia, Bhagirath; Talbot, Chad Lamar; Summers, Scott A. (Frontiers in Immunology, 2020)
Adipose depots are heterogeneous tissues that store and sense fuel levels. Through the secretion of lipids, cytokines, and protein hormones (adipokines), they communicate with other organ systems, informing them of the organism’s nutritional status. The adipose tissues include diverse types of adipocytes (white, beige, and brown) distinguished by the number/size of lipid droplets, mitochondrial density, and thermogenic capacity. Moreover, they include a spectrum of immune cells that modulate metabolic activity and tissue remodeling. The unique characteristics and interplay of these cells control the production of ceramides, a class of nutrient signals derived from fat and protein metabolism that modulate adipocyte function to regulate glucose and lipid metabolism. The excessive accumulation of ceramides contributes to the adipose tissue inflammation and dysfunction that underlies cardiometabolic disease. Herein we review findings on this important class of lipid species and discuss therapeutic possibilities of targeting these molecules to improve adipose health.